Protest Pedagogy - Dias, Beatrice (Radical Teacher, 2025)
When we occupy the streets for justice, we use collective power to take up space, both physically and ideologically. In this paper, I theorize protest as a construct of pedagogy through mirrored dimensions of protests in the streets. Within the context of a co-facilitated, online graduate course, I explore taking up epistemological space through intentionally complicating, questioning and expanding ways of knowing and building knowledge. This work draws from the rich lineage of counter-hegemonic narratives and collective power in Moraga & Anzaldúa’s This Bridge Called My Back, which epitomizes freedom possibilities unleashed when we speak the unspeakable as a pedagogy of protest.